(untitled) (Journal of the College of Basic Education, 2022)
Mathematical Morphology is a tool for extracting image components useful in the representation and description of region shape, such as boundaries, skeletons and convex hulls. The mathematical morphology depends on set theory and it can apply to binary images and gray scale images, and the usual set operators can be applied to them.The basic operation in mathematical morphology operate on two sets: the first one is the image, and the second one is the structuring element. The structuring element in practice is generally much smaller than the image, often 3x3 matrices